FAMILY HIPPOBOSCIDAE - Graciolli, Gustavo (Zootaxa, 2016)
This catalog presents 18 species distributed among 11 genera and two subfamilies of hippoboscid flies recorded in Colombia. For each genus we present synonymies and type species, and for each species account we present synonymies, disposition of type material, and specific localities, departments and, when available, the type-host.